The Influence of Learning Media and Learning Styles on Students 'Cognitive Learning Outcomes In Basic Faal Science Math In STKIP Muhammadiyah Kuningan - Hendro Setiadi Wiguna; Hartati Muchtar; Robinson Situmorang (International Journal of Education, Information Technology, and Others, 2020)
This study aims to determine the effect of learning media and learning styles on learning outcomes in the cognitive domain of students in basic physiology subjects. This study used a quasi-experimental method using a 2X2 factorial design. The findings indicate that: (1) the learning outcomes of students who use model learning media are higher than those of students who use image learning media (2) the learning outcomes of students who have a kinesthetic learning style are higher than the learning outcomes of students who have visual learning styles. (3) there is an influence of the interaction between learning media and learning styles on student cognitive learning outcomes in Basic Physiology courses. (4) cognitive learning outcomes of students who have a kinesthetic learning style who learn using model learning media are higher than realm learning outcomes. cognitive students who have a kinesthetic learning style who learn using image learning media. (5) cognitive learning outcomes of students who have visual learning styles who learn using learning media models are lower than those of students who have visual learning styles who learn using image learning media. (6) the cognitive learning outcomes of students who have a kinesthetic learning style who learn using model learning media are higher than the cognitive learning outcomes of students who have a visual learning style who learn using model learning media. (7) the cognitive learning outcomes of students who have a kinesthetic learning style who learn using image learning media are lower than the cognitive learning outcomes of students who have a visual learning style who learn using image learning media.